Longitudinal Study of Body Mass Index in Young Males and the Transition to Fatherhood. (November 2016) - Garfield, Craig F.; Duncan, Greg; Gutina, Anna; Rutsohn, Joshua; McDade, Thomas W.; Adam, Emma K.; Coley, Rebekah Levine; Chase-Lansdale, P. Lindsay
Despite a growing understanding that the social determinants of health have an impact on body mass index (BMI), the role of fatherhood on young men's BMI is understudied. This longitudinal study examines BMI in young men over time as they transition from adolescence into fatherhood in a nationally representative sample. Data from all four waves of the National Longitudinal Study of Adolescent Health supported a 20-year longitudinal analysis of 10, 253 men beginning in 1994. A "fatherhood-year" data set was created and changes in BMI were examined based on fatherhood status (nonfather, nonresident father, resident father), fatherhood years, and covariates. Though age is positively associated with BMI over all years for all men, comparing nonresident and resident fathers with nonfathers reveals different trajectories based on fatherhood status. Entrance into fatherhood is associated with an increase in BMI trajectory for both nonresident and resident fathers, while nonfathers exhibit a decrease over the same period. In this longitudinal, population-based study, fatherhood and residence status play a role in men's BMI. Designing obesity prevention interventions for young men that begin in adolescence and carry through young adulthood should target the distinctive needs of these populations, potentially improving their health outcomes.